If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(cx + 1) = 6x + 4 Reorder the terms: 3(1 + cx) = 6x + 4 (1 * 3 + cx * 3) = 6x + 4 (3 + 3cx) = 6x + 4 Reorder the terms: 3 + 3cx = 4 + 6x Solving 3 + 3cx = 4 + 6x Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3cx = 4 + -3 + 6x Combine like terms: 3 + -3 = 0 0 + 3cx = 4 + -3 + 6x 3cx = 4 + -3 + 6x Combine like terms: 4 + -3 = 1 3cx = 1 + 6x Divide each side by '3x'. c = 0.3333333333x-1 + 2 Simplifying c = 0.3333333333x-1 + 2 Reorder the terms: c = 2 + 0.3333333333x-1
| 6x+5+4x=66+4x | | -4=5t+6 | | (4x^2)+4=9 | | 5(5x-2)=153+2(20-2x) | | x+8=4.24 | | -6+8r=-6+8r | | S+26=8 | | x-6=-27 | | 0.2x+7.2=10 | | -3(2w-6)+4(-1-5w)=0 | | w*7*w*3*w=131 | | 40x^4-60x^3+20x=0 | | 5x-2=-3x+6 | | (3x+y)6= | | 5(y-2)-2=2(v+1)-5 | | 5B+3V=27.50 | | (x^2)-x-10=0 | | 4x^2+4=148 | | 5x-12-23x=6(-3x-2) | | 46-46x=(7x+3)(x-1) | | p=12x-5x | | 6-4x=4(1-x) | | 35-(2x-14)=40-(x+2) | | (2x^2)-x-(3)=0 | | 5x^2=23x+10 | | 40-7n=2(-5n+6)-n | | 8w/6+8=w-2 | | 12(4x-6)=8x+5(8x-6) | | 6s=-3T | | 5s=8t+12 | | 4(2x-1)-(-3x-5)=-179 | | 10b+5=76+5 |